Implementasi Pengembangan Sistem Media Pembelajaran Pengenalan Komputer: Program Studi Sistem Informasi Universitas PGRI Madiun - Setiawan, Dimas; Arifin, Irsyadul; Ardianto, Rian (Universitas Nusantara PGRI Kediri, 2018)
The development of educational technology is growing rapidly, this is happening with the growing trend in the trend of online learning technology, mobile & multimedia. In the course of logic and program algorithm, students are introduced about the introduction of computer technology, in order to create a technology-based educational environment then made learning media introduction computer, made possible by the learning media, computer introduction, can help the learning process in the course of logic & programming algorithm.